Teaching African literature and access to digital media and devices in Gauteng schools - Mahao, Mahao (My University, 2019)
The relationship between technology and classroom practices has become one of the major pre-occupations of modern scholarship; especially in the era where technology is increasingly maintaining a firm grip on different spheres of human life. This study explores the use of digital media and devices in the teaching and learning of African literature (in English) in selected Gauteng schools. This is in the context where the Department of Basic Education (DBE) in South Africa has advocated for the Africanisation of the literature syllabus by prescribing more African texts as opposed to the previous era where European and American texts were predominant. The study explores the use of digital media and devices in researching and teaching African literary novel and drama texts in nine Gauteng high school classrooms. It also examines the potential for digital media and devices in literature classrooms. As the DBE recommends a major shift from Western to African literature, what are the implications regarding access to resources, especially digital (both devices and information sites) for teachers as they navigate their way through the texts? This relates mainly to research, planning and execution of the literature lesson. The study is qualitative and data was collected through questionnaires, semi-structured interviews, selected classroom observations and environmental assessment of the schools. All nine high schools were purposefully sampled and thematic content analysis was used to analyse data. The results show that in the sampled schools, African literature (and literature in general) is increasingly being taught and learned through the use of digital media and devices, with the cellphone also emerging as one of the ubiquitous and key devices used in research, teaching and learning. However, despite observable access by teachers to digital media and devices, web-based resources for African literature are perceived to be severely limited and a gap is identified to give African literary texts more online presence. Equally important is the contribution the study makes as possibly the first of its kind to focus solely on African literature and digital media. Additionally, there is very little evidence that technology engenders collaborative activities in literature lessons and among learners. The study finds – based on literature and empirical evidence – that while some teachers are still reluctant to use digital media and devices, it is becoming increasingly difficult for literature teachers to plan and execute their lessons without these resources. On pedagogical practice, the study concludes that teachers’ digital skills and access to devices and online resources do not appear to instigate a move towards lessons where higher-order thinking and problem-solving are the hallmarks of digitally-aided instruction.
A thesis submitted to the Wits School of Education, Faculty of Humanities University of the Witwatersrand, Johannesburg in fulfillment of the degree of Doctor of Philosophy Johannesburg, 2019